(untitled) - McCorry, Kieran (Burlinton, MA, 2006)
This book covers, in detail, the tools and techniques that messaging system planners and administrators will require in order to establish a functioning interoperability environment between Exchange 2003 and previous versions of Exchange including Exchange 5.5 and Exchange 2000
Keywords: Client/server computing,Máy tính cục bộ / máy chủ